Éléments conversationnels du clavardage : un entraînement à l'expression orale pour les apprenants de langues à distance ? - Vincenza Tudini (ALSIC: Apprentissage des Langues et Systèmes d'Information et de Communication)
A critical issue in the delivery of language courses at a distance is to provide adequate scaffolding and monitoring1 of learners to assist them in the development of their interlanguage. As well as being one of the main reasons students enroll in language courses, oral interaction is considered beneficial to interlanguage development since it provides opportunities for negotiation of meaning. In the case of campus-based students, learners' progress in speaking the target language is supported and monitored mainly in the classroom. If non campus-based or online students do not attend face-to-face classes, how do they find opportunities for oral interaction? Using a Conversational Analysis and Second Language Acquisition perspective, the author considers elements which are common to both face-to-face oral interactions and chatting via a computer, with a view to assessing the potential of synchronous text-based communication tools to support the development of the speaking skills and interlanguage of distance language learners. This is done by reviewing findings of previous studies on synchronous text-based communication tools and identifying selected characteristics of oral interaction which are present in the chat sessions of two groups of campus-based intermediate level learners of Italian. In particular, the study focuses on repairs and incorporation of target forms, variety of speech acts, particularly questions and clarification requests, and the presence of discourse markers.